Status of social sciences in the vernacular languages in North East India - Singh, Jai Prakash, 1939-; Syiemlieh, David R. (David Reid); Thomas, C. Joshua; Indian Council of Social Science Research. North Eastern Regional Centre; Seminar on the Status of Social Sciences in the Vernacular Languages of North East India (1998 : ICSSR-NERC) (New Delhi : Regency Publications, 2000)
Papers presented at the Seminar on the Status of Social Sciences in the Vernacular Languages of North East India in 1998, organised by ICSSR-NERC.
Companion volume to Trends in social sciences and humanities in North East India, 1947-97.
Includes bibliographical references.
Keywords: Social sciences -- India, Northeastern -- Congresses; Humanities -- India, Northeastern -- Congresses